Three-year postoperative outcomes between MIS and conventional TLIF in1-segment lumbar disc herniation. Issue 3 (4th May 2017) - Lv, You; Chen, Jingyang; Chen, Jinchuan; Wu, Yuling; Chen, Xiangyang; Liu, Yi; Chu, Zhaoming; Sheng, Luxin; Qin, Rujie; Chen, Ming
Abstract: Aim: The aim of this study is to assess the long-term clinical and radiological outcomes between minimally invasive (MIS) and conventional transforaminal lumbar interbody fusion (TLIF) in treating one-segment lumbar disc herniation (LDH). Material and methods: One-hundred and six patients treated by MIS-TLIF (50 cases) or conventional TLIF (56 cases) were included. Perioperative results were evaluated. Clinical outcomes were compared preoperatively and postoperatively. Radiologic parameters were based on a comparison of preoperative and three-year postoperative lumbar lordosis, segmental lordosis, sacral slope, the cross-sectional area of the paraspinal muscle and fusion rates. Results: MIS TILF had significantly less blood, shorter operation time, mean return to work time and lower intramuscular pressure compared with the conventional group during the operation. VAS scores for lower back pain and ODI in MIS-TLIF were significantly decreased. The mean cross-sectional area of the paraspinal muscle was significantly decreased after surgery in the conventional TLIF group and no significant intragroup differences were established in the MIS-TLIF group. No significant differences were found in fusion rate, lumbar lordosis, segmental lordosis and sacral slope. Conclusions: Both MIS and conventional TLIF were beneficial for patients with LDH. However, MIS-TLIF manifests a great improvement in perioperative outcomes, low back pain, disability and preventing paraspinal muscle atrophy during the follow-up period observation.